(untitled) (The Research of Medical Science Review, 2025)
Diabetic nephropathy (DN) is a predominant consequence of type 2 diabetes mellitus (T2DM), with visceral obesity contributing to its development through metabolic dysfunction. The Visceral Adiposity Index (VAI), an indicator of visceral fat, may assist in predicting diabetic nephropathy risk; however, local data is limited. OBJECTIVE: To determine the frequency of nephropathy among diabetic patients presenting with various levels of visceral adiposity index (VAI) to the tertiary care hospital of Rawalpindi. SUBJECTS AND METHODS: This cross-sectional study was performed at Fauji Foundation Hospital, Rawalpindi. 173 patients having Type 2 Diabetes Mellitus (HbA1c >6.5%) from one year or more were enrolled. VAI was computed with sex-specific formulas that included waist circumference, BMI, triglycerides, and HDL-C, categorizing patients into three levels: VAI <1.45 (Level 1), 1.45–2.65 (Level 2), and >2.65 (Level 3). Diabetic nephropathy was diagnosed using eGFR (<60 mL/min/1.73m²) or albuminuria (UACR ≥30 mg/g). Gathered data was analyzed utilizing SPSS v20. Stratification was done for study confounders. Chi-square test was applied to evaluate relationships and p≤0.05 considered significant. RESULTS: The incidence of diabetic nephropathy escalated with elevated VAI levels. At VAI level 1, merely 19.1% of patients exhibited diabetic nephropathy, in contrast to 53.5% at level 2 and 64.7% at level 3. In total, 42.2% of patients received a diagnosis of diabetic nephropathy. Females had elevated DN rates at all VAI levels (p=0.001). Age stratification indicated substantial diabetic nephropathy in older patients (>55 years) with elevated VAI (p=0.001), whereas extended diabetes duration (≥27 months) and inadequate glycemic control (HbA1c ≥10.0%) reinforced the correlation (p≤0.001 and p=0.009, respectively). CONCLUSION: Increased VAI is significantly associated with the incidence of DN, especially in females, individuals with poorly managed diabetes, and those with an extended course of the disease. VAI, an uncomplicated and economical instrument, has the potential to improve early diabetic nephropathy risk categorization in resource-constrained environments, facilitating targeted therapies to alleviate renal consequences. Future investigations are required to confirm causality and refine VAI levels.